2013
DOI: 10.1002/ijc.28390
|View full text |Cite
|
Sign up to set email alerts
|

CHFR silencing or microsatellite instability is associated with increased antitumor activity of docetaxel or gemcitabine in colorectal cancer

Abstract: Phenotypic differences among cancers with the same origin may be associated with chemotherapy response. CHFR silencing associated with DNA methylation has been suggested to be predictive of taxane sensitivity in diverse tumor types. However, the use of microsatellite instability (MSI:unstable--MSS:stable) as a predictive marker for therapeutic effect has had conflicting results. We examined these molecular alterations as predictors of chemotherapy sensitivity in colorectal cancer (CRC). Differential sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
(95 reference statements)
1
15
0
Order By: Relevance
“…We furthermore show that this interaction is mediated by CHFR's PBZ domain and that its disruption either by mutation of the PBZ domain or PARP1 knockdown leads to auto-ubiquitination and subsequent proteasomal degradation of CHFR. Together with previously published results that reduced CHFR expression in lung cancer is associated with improved survival following platinum taxane based therapy [ 6 ] and that taxane sensitivity is increased in gastric [ 1 ]-, colon [ 2 ]- and cervical cancers [ 22 ] in which CHFR is silenced epigenetically, we proposed a model in which pharmacologic inhibition of the CHFR-PARP1 interaction with subsequent loss of CHFR and disruption of antephase checkpoint function helps to overcome intrinsic taxane resistance across a wide spectrum of different tumor types (Figure 7 ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We furthermore show that this interaction is mediated by CHFR's PBZ domain and that its disruption either by mutation of the PBZ domain or PARP1 knockdown leads to auto-ubiquitination and subsequent proteasomal degradation of CHFR. Together with previously published results that reduced CHFR expression in lung cancer is associated with improved survival following platinum taxane based therapy [ 6 ] and that taxane sensitivity is increased in gastric [ 1 ]-, colon [ 2 ]- and cervical cancers [ 22 ] in which CHFR is silenced epigenetically, we proposed a model in which pharmacologic inhibition of the CHFR-PARP1 interaction with subsequent loss of CHFR and disruption of antephase checkpoint function helps to overcome intrinsic taxane resistance across a wide spectrum of different tumor types (Figure 7 ).…”
Section: Discussionsupporting
confidence: 75%
“…Unfortunately, primary resistance to taxanes is common and poses an important clinical problem. The mitotic checkpoint gene “checkpoint with forkhead and ringfinger domains” (CHFR) has recently emerged as a critical mediator of resistance against microtubular-targeted therapies in various different cancer types including gastric-[ 1 ], colon-[ 2 , 3 ], endometrial-,[ 4 , 5 ] and lung cancer [ 6 ]. Epigenetic silencing of CHFR by promoter hypermethylation or reduced protein expression have been described as predictive biomarkers for taxane sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, we and others were able to show that GEM exerts direct toxic effects towards MMR-D tumor cells of different origin (i.e. solid tumor vs. hematological malignancies) [27, 28]. Inhibition of cell proliferation was achieved at concentrations well below plasma levels under standard therapy [27] and accompanied by classical signs of ICD induction (exposure of CalR, HMGB1 release), the latter shown here on three low-passage murine MMR-D cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of CHFR is observed in breast, bladder, colorectal, gastric, nasopharyngeal, lung, esophageal, cervical, hepatocellular, oral squamous, head and neck, and endometrial cancer [ 152 ]; and is a potential marker of taxane sensitivity for many cancer types. In vitro evidence using nasopharyngeal carcinoma, colorectal cancer, esophageal, endometrial cancer, and gastric cancer cell lines suggests that CHFR hypermethylation contributes to docetaxel and paclitaxel sensitivity [ 153 , 154 , 155 , 156 , 157 ]. However, subsequent clinical studies have not shown a clear influence of CHFR methylation on taxane sensitivity.…”
Section: Epigenetic Markers Informing Therapeutic Decision-makingmentioning
confidence: 99%